Research Brief: Value chain and market potential of Bambara groundnut to strengthen climate resilience, food security and women’s income in Mali - Mbosso, C.; Berthe Niang, Aminata; Mohamadou, Y.; Padulosi, S.; Sidibé, A.; Meldrum, G. (Bioversity International, 2018)
This value chain analysis was carried out by Charlie Mbosso in collaboration with Aminata Berthe Niang, Youssoufa Mohamadou, Stefano Padulosi, Amadou Sidibe, and Gennifer Meldrum as part of the project "Linking Value Chains of Agricultural Biodiversity to Adaptation to Climate Change and Nutrition: Empowering the Poor for Risk Management "funded by the International Fund for Agricultural Development (IFAD), the European Union (EU) and the Research Programs of CGIAR Centers on Climate Change, Agriculture and Security (CCAFS) and Agriculture for Nutrition and Health (A4NH)